PRODUKSI BIODISEL DARI MINYAK GORENG BEKAS MENGGUNAKAN KATALIS CaO CANGKANG KERANG DARAH KALSINASI 900 °C - Rini Setiowati; Nurhayati '; Amilia Linggawati (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2014)
Biodiesel is one of the most potential alternative energy for diesel machine since it isrenewable and environmental friendly. Biodiesel can be produced by transesterificationreaction of vegetable oil or animal fat with alcohol and catalyst addition. In this study,biodiesel was produced by transesterification reaction of waste cooking oil andmethanol using a CaO catalyst of blood cockle shells (Anadara granosa). Blood cockleshells (Anadara granosa) can be used as heterogeneous catalysts for biodieselproduction because it contains CaCO 3 that can be decomposed into CaO.Decomposition of the blood cockle shells as heterogeneous catalyst for biodieselproduction was carried out at 900 oC for 5 hours. The yield of biodiesel optimum was81.67% with 3% weight of catalyst, 1:15 of oil and methanol mole ratio, 3 hours ofreaction time and 60±2 oC of reaction temperature.